Implementation of Guard Duty during Loading and Unloading Process to Avoid Damage to Cargo on MV. Dahlia Merah - Selele, Ahmad Abdalla; Thabit, Samir (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2025)
The globalization of the world in this era has had a great impact on the order and regulations of life. In general, the task of a watch officer when the ship is anchored or loading and unloading are not only to monitor the conditions around the ship but also to supervise the loading and unloading process so that no errors occur, the watch officer must always know about his duties and responsibilities when the ship is loading and unloading because if a mistake or negligence occurs from a watch officer it will cause a big problem. Sometimes the orders made by the Captain (Master Standing Order) cannot be fully carried out by the crew who are on guard duty so this negligence can cause losses to the company and the cargo owner. This study uses a descriptive qualitative approach, which aims to describe the phenomenon in depth based on data obtained from the field. The results of this study are as follows: 1) How to avoid damage during loading and unloading on the MV. Dahlia Merah includes proper preparation, worker training, careful handling, optimal space arrangement, weather and environmental monitoring, supervision during the process, good collaboration, inspection after loading and unloading; and 2) Obstacles and solutions in carrying out loading and unloading according to procedures on the MV. Dahlia Merah as follows: a) Obstacles, including delays in the administrative process, bad weather, limited port facilities, equipment problems, compliance with occupational health and safety (K3) procedures, communication problems, challenges in arranging goods; b) Solutions, including improving the administration system, real-time weather monitoring, improving port infrastructure, equipment maintenance and care, improving K3 procedures, a more efficient communication system, and managing goods with technology.